1999
DOI: 10.1007/s005200050245
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of tamoxifen with concurrent cytotoxic adjuvant treatment affects lymphocytes and lymphocyte subsets counts in breast cancer patients

Abstract: The effects and interaction of endocrine and cytotoxic adjuvant treatment on measures of cellular immunity were assessed in 41 stage I-II breast cancer patients from International Breast Cancer Study Group trials. Counts of lymphocytes and lymphocyte subsets [(T, T4, T8, B, natural killer (NK) and activated T (AT) cells] were assessed by flow cytometry immediately before adjuvant therapy at baseline and on day 1 of the 3rd cycle. Twenty-two patients received cyclophosphamide, methotrexate and 5-fluorouracil (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 19 publications
(19 reference statements)
0
6
0
Order By: Relevance
“…Fludarabine, a nucleoside drug used in hematologic cancers, produces a profound and persistent depletion in T cell (CD4+) populations 20, 21. Furthermore, Stages I and II breast carcinoma survivors who received cyclic chemotherapy (CMF‐cyclophosphamide, methotrexate, and 5‐fluorouracil) have been shown to depress total lymphocyte counts as well as decrease T cells (CD4+, CD8+), B cells (CD19+), NK cells (CD3–CD16+CD56+), and activated T cells 22. Similarly, Sewell et al showed that breast carcinoma survivors who received cyclic CMF had decreased numbers of T cells (CD4+) and B cells (CD19+), as well as reduced functional capacity in NK cells and lymphokine‐activated killer (LAK) cells that persisted for up to six months following cessation of therapy 23…”
Section: Immune System Response To Tumorsmentioning
confidence: 99%
“…Fludarabine, a nucleoside drug used in hematologic cancers, produces a profound and persistent depletion in T cell (CD4+) populations 20, 21. Furthermore, Stages I and II breast carcinoma survivors who received cyclic chemotherapy (CMF‐cyclophosphamide, methotrexate, and 5‐fluorouracil) have been shown to depress total lymphocyte counts as well as decrease T cells (CD4+, CD8+), B cells (CD19+), NK cells (CD3–CD16+CD56+), and activated T cells 22. Similarly, Sewell et al showed that breast carcinoma survivors who received cyclic CMF had decreased numbers of T cells (CD4+) and B cells (CD19+), as well as reduced functional capacity in NK cells and lymphokine‐activated killer (LAK) cells that persisted for up to six months following cessation of therapy 23…”
Section: Immune System Response To Tumorsmentioning
confidence: 99%
“…These studies indicate that each chemotherapy regimen has a different effect on immunological parameters [9][10][11]. The results of studies on patients, however, cannot be extrapolated to occupational exposures.…”
Section: Introductionmentioning
confidence: 99%
“…For example, lymphocyte depletion in human patients undergoing chemotherapy has been reported, but the degree of lymphocyte depletion appeared to be dependent on the particular chemotherapy protocol. [1][2][3][4] Lymphocyte depletion, specifically, depletion of CD4 + T cells, may persist long after completion of chemotherapy. 5,6 Not all chemotherapy agents are equally immunosuppressive.…”
mentioning
confidence: 99%